Value Co-Creation in ICT Services Company: A Case Study of a Cross-Border Acquisition. Issue 4 (2nd October 2018) - Heim, Irina; Han, Tian; Ghobadian, Abby
Abstract: Post-merger and acquisition (M&A) integration is especially important for the services industry, where value co-creation between actors plays a crucial role. This paper is a qualitative single case study of a multinational company (MNE) in information technology (ICT) industry, and the post-acquisition processes of its subsidiary in Russia. The main contribution of this article is the application of a value co-creation view, to the settings of the international business. We also identify the actors and their roles and activities in the value co-creation in the Russian context.